Dust is the dominant source of "heavy metals" to peat moss (Sphagnum fuscum) in the bogs of the Athabasca Bituminous Sands region of northern Alberta. (July 2016) - Shotyk, William; Bicalho, Beatriz; Cuss, Chad W.; Duke, M. John M.; Noernberg, Tommy; Pelletier, Rick; Steinnes, Eiliv; Zaccone, Claudio
Abstract: Sphagnum fuscum was collected from twenty-five ombrotrophic (rain-fed) peat bogs surrounding open pit mines and upgrading facilities of Athabasca Bituminous Sands (ABS) in northern Alberta (AB) in order to assess the extent of atmospheric contamination by trace elements. As a control, this moss species was also collected at a bog near Utikuma (UTK) in an undeveloped part of AB and 264 km SW of the ABS region. For comparison, this moss was also collected in central AB, in the vicinity of the City of Edmonton which is approximately 500 km to the south of the ABS region, from the Wagner Wetland which is 22 km W of the City, from Seba Beach (ca. 90 km W) and from Elk Island National Park (ca. 45 km E). All of the moss samples were digested and trace elements concentrations determined using ICP-SMS at a commercial laboratory, with selected samples also analyzed using instrumental neutron activation analysis at the University of Alberta. The mosses from the ABS region yielded lower concentrations of Ag, As, Bi, Cd, Cu, Pb, Sb, Tl, and Zn compared to the moss from the Edmonton area. Concentrations of Ni and Mo in the mosses were comparable in these two regions, but V was more abundant in the ABS samples. Compared with the surface vegetation of eight peat cores collected in recent years from British Columbia, Ontario, Quebec and New Brunswick, the mean concentrations of Ag, As, Bi, Cd, Cu, Mo, Ni, Pb, Sb, Tl and Zn in the mosses from the ABS region are generally much lower. In fact, the concentrations of these trace elements in the samples from the ABS region are comparable to the corresponding values in forest moss from remote regions of central and northern Norway. Lithophile element concentrations (Ba, Be, Ga, Ge, Li, Sc, Th, Ti, Zr) explain most of the variation in trace metal concentrations in the moss samples. The mean concentrations of Th and Zr are greatest in the moss samples from the ABS region, reflecting dust inputs to the bogs from open pit mines, aggregate quarries, and gravel roads. Linear regressions of V, Ni, and Mo (elements enriched in bitumen) versus Sc (a conservative, lithophile element) show excellent correlations in the mosses from the ABS region, but this is true also of Ag, Pb, Sb and Tl: thus, most of the variation in the trace metal concentrations can be explained simply by the abundance of dust particles on the plants of this region. Unlike the moss samples from the ABS region and from UTK where Pb/Sc ratios resemble those of crustal rocks, the moss samples from the other regions studied yielded much greater Pb/Sc ratios implying significant anthropogenic Pb contributions at these other sites. Highlights: Peat moss ( Sphagnum fuscum ) from bogs was used to monitor atmospheric deposition. Moss was collected near bitumen mines and upgraders in northern Alberta (AB). Moss from this industrial region contained lower concentrations of Ag, As, Bi, Cd, Cu, Pb, Sb, Tl, and Zn compared to moss from central AB. Peat moss from northern AB is similar in composition to forest moss from remote central and northern Norway. Lithophile elements (Ba, Be, Ga, Ge, Li, Sc, Th, Ti, Zr) identify dust as the most important source of trace elements to the moss.